PENGARUH KESELAMATAN KERJA FISIK DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN - Setiawan, Iwan; Khurosani, Aan (Jurnal Riset Bisnis dan Manajemen Tirtayasa, 2018)
Today's steel industry is very competitive competition. Therefore, each company is required to improve the quality and make the right business strategy to improve company performance. This study aims to clarify the effect of occupational safety and the working environment of the job performance and job satisfaction as an intervening variable in PT. Krakatau Posco. Cilegon Banten. The study was conducted by taking samples using non-probability sampling technique, which is a technique that does not provide opportunities or equal opportunity for each element or member of the population to be selected into the sample. While the technique of taking informants using purposive sampling technique is a technique for determining sample with some specific considerations that aim that the data obtained will be more representative. Collecting respondent data obtained from 90 employees of PT. Krakatau Posco Cilegon, with a questionnaire consisting of questions and statements. Respondents' answers to questions and statements were analyzed qualitatively and quantitatively, and the answers were analyzed with methods of data analysis techniques Partial Least Square using version SmartPLS 2.0.m3. The analysis showed that the effect of occupational safety on job satisfaction is positive and significant. Furthermore, that the effect on job satisfaction working environment that is positive and significant. Occupational safety and influence on the performance of the work that is positive and significant. And the influence of the working environment on the performance of the work as well as a positive and significant effect of job satisfaction on job performance positively and significantly.